2014
DOI: 10.3389/fnbeh.2014.00423
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the oxytocin receptor gene is associated with behavioral and neural correlates of empathic accuracy

Abstract: The neuromodulators oxytocin and serotonin have been implicated in regulating affective processes underlying empathy. Understanding this dependency, however, has been limited by a lack of objective metrics for measuring empathic performance. Here we employ a novel psychophysical method for measuring empathic performance that quantitatively measures the ability of subjects to decode the experience of another person's pain. In 50 female subjects, we acquired functional magnetic resonance imaging data as they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 59 publications
(95 reference statements)
0
29
1
1
Order By: Relevance
“…Alleles of rs53576 have been reported in several studies: the G allele has been reported to be implicated in Bullimia Nerviosa 73 , but also in diminished stress after social support 74 , adult separation anxiety 75 , oxytocin sensitivity in social cooperation settings (increased in males, decreased in females) 76 , overall weak social cognition skills in ADHD patients 25 and facial recognition deficits 53 . MHS rs53576(A) might be involved in AS 27, 45 , higher empathic performanc 77, 78 and social connectedness in women 31 , but also lower psychological resources such as self-esteem, optimism and emotional mastery 79 . Though the literature on rs53576 doesn’t provide unequivocal results, there seems to be consensus on this SNP being dependent on environmental factors: the G allele appears to affect social sensitivity; adverse life conditions can lead to negative (non-prosocial) behavior in G carriers, but the opposite effect has also been reported 80 .…”
Section: Resultsmentioning
confidence: 99%
“…Alleles of rs53576 have been reported in several studies: the G allele has been reported to be implicated in Bullimia Nerviosa 73 , but also in diminished stress after social support 74 , adult separation anxiety 75 , oxytocin sensitivity in social cooperation settings (increased in males, decreased in females) 76 , overall weak social cognition skills in ADHD patients 25 and facial recognition deficits 53 . MHS rs53576(A) might be involved in AS 27, 45 , higher empathic performanc 77, 78 and social connectedness in women 31 , but also lower psychological resources such as self-esteem, optimism and emotional mastery 79 . Though the literature on rs53576 doesn’t provide unequivocal results, there seems to be consensus on this SNP being dependent on environmental factors: the G allele appears to affect social sensitivity; adverse life conditions can lead to negative (non-prosocial) behavior in G carriers, but the opposite effect has also been reported 80 .…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in the OXTR gene have also been differentially correlated with emotional (209)(210)(211)(212) or cognitive (209,210,(213)(214)(215), empathy. Although these findings suggest the possibility that both types of empathy are regulated by OT, they must be viewed with caution because, as noted above, a recent meta-analysis has found that OXTR polymorphisms failed to explain a significant part of human social behaviour (77).…”
Section: Parallel Processing Of Emotional and Cognitive Empathymentioning
confidence: 99%
“…There is evidence that impairments in empathy within these groups have a significant influence on the individual's social and community function, beyond the effects of general cognition or symptoms (17,18). Empathy is partially heritable (19) and variance in empathic performance has been linked to polymorphisms of the oxytocin receptor gene (20)(21)(22). However, developmental effects on empathy are profound in early childhood and adolescence (23,24) and are dependent on environmental and experiential factors like family environment, maternal synchrony and mimicry (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%